2010
DOI: 10.1007/s11430-010-0056-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics and response to climate change of Larix Miller tree-ring in China

Abstract: As one of the earliest species used in dendrochronological studies, Larix responds sensitively to climate change. In this study, nine larch species and one variety from eleven sites were collected to study the growth characteristics of tree-ring width using dendrochronological methods. Ten residual tree-ring chronologies were developed to analyze their relationships with regional standardized anomaly series by Pearson's correlation analysis. The results suggest that most of the chronologies had significantly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
4
9
0
Order By: Relevance
“…3). This is consistent with the results presented for Larix Miller in China, i.e., a positive correlation with the temperature in spring [33]. From the perspective of plant physiology, as the temperature gradually increases in April, new leaves begin to develop and the xylem cells begin to divide and grow, which would promote the growth of Quercus acutissima and is conducive to the formation of earlywood.…”
Section: Effects Of Average Monthly Temperature and Precipitation On supporting
confidence: 91%
“…3). This is consistent with the results presented for Larix Miller in China, i.e., a positive correlation with the temperature in spring [33]. From the perspective of plant physiology, as the temperature gradually increases in April, new leaves begin to develop and the xylem cells begin to divide and grow, which would promote the growth of Quercus acutissima and is conducive to the formation of earlywood.…”
Section: Effects Of Average Monthly Temperature and Precipitation On supporting
confidence: 91%
“…At the end of the preceding growing season, less precipitation prior to defoliation can bring about more light input for photosynthesis, resulting in more net primary production stored for the next growing season. The negative effects of precipitation during autumn of the previous year on growth of this species have also been reported in the Wutai and Lüliang Mountains, both approximately 150 km from our study area [4,33].…”
Section: Species-dependent Growth In Response To Climatesupporting
confidence: 82%
“…In this study, the tree-ring maximum density of Dahurian larch near the treeline revealed a strong relationship with mean maximum temperature during May-August, which was very similar to the results of Schrenk Larch in the Tianshan Mountains at high altitudes in northwestern China [20]. From a physiological perspective, the tree cambium develops tracheids and lengthens rapidly the earlywood cells in the early growing season, representing tree-ring width sensitive to winter and spring temperatures prior to the current growing season [13,15,41]. During the later part of the growing season, radial growth of trees tends to process cellwall thickening and nutrition accumulation.…”
Section: Discussionsupporting
confidence: 61%